Gobernanza global y las nuevas formas de construir consensos multilaterales: El G20 financiero bajo la lupa - Botto, Mercedes Isabel (2012)
Based on the idea that international organizations are strongly determined by their historical context, this paper analyses the impact of the g20 on global governance. In so doing, it compares the post II world war order, characterized by formal multilateral institutions, and the new global order, where minilateral institutions tend to predominate. Findings show the emergence of a new way of building global consensus, in which democratic legitimacy criteria are enhanced whereas decision making effectiveness is still a pending issue.